2003
DOI: 10.1002/da.10117
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alexithymic features on response to antidepressant medication in patients with major depression

Abstract: There has been no follow-up study regarding the effect of alexithymic features on antidepressant treatment. This study was planned to observe whether alexithymia effects short-term treatment outcome in depression. The study included 32 alexithymic and 33 nonalexithymic outpatients with major depression. Depression was assessed on the basis of the Structured Clinical Interview for DSM-IV (SCID-I). Level of depression was measured using the 17-item Hamilton Rating Scale for Depression (HAM-D). Alexithymia was sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Earlier studies [5,9,25] have suggested that alexithymia in depressed patients might be alleviated during recovery from depression. Similarly, a recent study among pregnant women showed that although TAS scores did not predict depression, they increased during depression and decreased after remission [26].…”
Section: Discussionmentioning
confidence: 98%
“…Earlier studies [5,9,25] have suggested that alexithymia in depressed patients might be alleviated during recovery from depression. Similarly, a recent study among pregnant women showed that although TAS scores did not predict depression, they increased during depression and decreased after remission [26].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, alexithymia seems to have some influence on treatment responses (32). One theory for a causal relationship between alexithymia and psychosomatic illnesses, for example, is that alexithymics may lack the so-called affective awareness which would permit identification of a particular situation as stressful, and they therefore experience stressful events longer and more frequently than non-alexithymics; this, in turn, may lead to a cascade of increased or excessive sympathetic activity, tissue damage, and pain (33).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically oriented research suggests that alexithymic depressed patients constitute a specific group: irrespective of the degree of depression, they have more suicidal ideation [9] , more somatic symptoms of distress [10] and respond significantly less well to the antidepressant medication paroxetine than nonalexithymic depressed patients [11] . A categorical distinction has also been suggested by clinicians who discriminate between primary and secondary depression [12] or between essential and psychoneurotic depression [13] .…”
mentioning
confidence: 99%